2020
DOI: 10.1002/pbc.28367
|View full text |Cite
|
Sign up to set email alerts
|

Race and socioeconomic status in pediatric allogeneic hematopoietic cell transplantation for nonmalignant conditions

Abstract: Background Survival disparities by race/ethnicity and socioeconomic status (SES) are observed in a wide range of pediatric treatment settings including oncology and solid organ transplantation. To date, few studies have examined the effects of race and SES on outcomes in pediatric allogeneic hematopoietic cell transplantation (HCT). We explored whether survival differed by race/ethnicity or SES in children receiving HCT for nonmalignant conditions at a single institution serving a diverse patient population. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The findings of this study have substantial implications in clinical practice. Routine assessments should be conducted early and often throughout the pediatric HCT course to identify patients and families who are at risk of disparate medical outcomes related to SDoH 21 . Such assessments could be used to tailor the interventions and resources provided to patients and families by a multidisciplinary team.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study have substantial implications in clinical practice. Routine assessments should be conducted early and often throughout the pediatric HCT course to identify patients and families who are at risk of disparate medical outcomes related to SDoH 21 . Such assessments could be used to tailor the interventions and resources provided to patients and families by a multidisciplinary team.…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric surgery studies reporting this outcome are particularly sparse. Harney et al 25 reported no racial disparities in pediatric allogeneic hematopoietic cell transplantation for nonmalignant conditions and suggested that this could be due to the mitigation of typical drivers of racial health disparities at their tertiary care center through access to high-quality medical and supportive care. Similarly, our institution offers services such patient education, transportation assistance, trained interpreters, and financial support.…”
Section: Discussionmentioning
confidence: 99%
“…112 A multidisciplinary approach including psychosocial and sociodemographic assessments can help mitigate these challenges. 113 Data from the Center for International Blood and Marrow Transplant Research suggest inferior access to transplantation for adult Americans with lymphoproliferative disease who come from disadvantaged areas. 114 Nevertheless, there are no data on the effect of health coverage status on access to transplantation.…”
Section: Social Determinants Of Prevention and Diagnosis Of Primary I...mentioning
confidence: 99%